1997
DOI: 10.1128/jcm.35.2.418-421.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification and serotyping of Ornithobacterium rhinotracheale

Abstract: In the present study 443 strains of Ornithobacterium rhinotracheale, a causative agent of respiratory disease in fowl, were investigated biochemically and serologically. In both ways O. rhinotracheale could be differentiated from other gram-negative rods and, more particularly, from the Pasteurella-like bacteria potentially pathogenic for fowl. For the biochemical characterization of O. rhinotracheale the API 2ONE identification strip proved to be useful, although O. rhinotracheale is not included in the API s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 6 publications
2
52
0
1
Order By: Relevance
“…Serotyping is the traditional method of distinguishing O. rhinotracheale isolates (van Empel & Hafez, 1999). Consistent with data in the literature (van Empel et al, 1997;Numee et al, 2012), serotype A was the most prevalent serotype among the strains isolated in Hungary in 1997-2015. Most of the isolates from turkeys and those from birds of prey belonged to this group.…”
Section: Discussionsupporting
confidence: 80%
“…Serotyping is the traditional method of distinguishing O. rhinotracheale isolates (van Empel & Hafez, 1999). Consistent with data in the literature (van Empel et al, 1997;Numee et al, 2012), serotype A was the most prevalent serotype among the strains isolated in Hungary in 1997-2015. Most of the isolates from turkeys and those from birds of prey belonged to this group.…”
Section: Discussionsupporting
confidence: 80%
“…The use of ELISA for the detection of antibodies to O. rhinotracheale has been reported (Hafez and Sting, 1996;van Empel et al, 1997;van Empel and Hafez, 1999). The serotype specificity of the ELISA is a disadvantage, although a number of commercial ELISAs have been described to have high sensitivity to various O. rhinotracheale serotypes (van Empel and Hafez, 1999;Lopes et al, 2000;Heeder et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As no O. rhinotracheale vaccine is used in Iran, positive reactions in ELISA are indicative of field infections. Because, the commercial ELISA used in this study was able to detect only 12 out of 18 identified O. rhinotracheale serotypes (van Empel et al, 1997), it is possible that some of the O. rhinotracheale infected chicken sera may have remained undetected and level of infection to O. rhinotracheale are much higher.…”
Section: Discussionmentioning
confidence: 99%
“…ORT can be a primary or secondary etiological agent, depending on the strain virulence, environmental factors, the immune status of the host, and the presence of other infectious agents [1]. In recent years, outbreaks of respiratory disease associated with ORT have been reported all over the world, including the USA, France, Netherlands, Belgium, Spain, Germany, Hungary, Israel, Korea, Japan, Taiwan, Turkey, Brazil, Iran and South Africa [1][2][3][4][5][6][7][8][9]. This pathogen can cause economic losses in the poultry industry due to growth retardation and the designation of infected carcasses as unacceptable for human consumption [1,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, outbreaks of respiratory disease associated with ORT have been reported all over the world, including the USA, France, Netherlands, Belgium, Spain, Germany, Hungary, Israel, Korea, Japan, Taiwan, Turkey, Brazil, Iran and South Africa [1][2][3][4][5][6][7][8][9]. This pathogen can cause economic losses in the poultry industry due to growth retardation and the designation of infected carcasses as unacceptable for human consumption [1,6,8]. The H9N2 avian influenza virus (AIV) is not only widespread in poultry, but it also has important implications for human health as a zoonotic infection [10,11].…”
Section: Introductionmentioning
confidence: 99%